Upaya Meningkatkan Minat dan Hasil Belajar Sejarah Kebudayaan Islam Melalui Penerapan Student Teams Achievement Divisions (STAD) - Iskandar, Iskandar; Murziqin, Ramzi (Jurnal Nispatti, 2024)
The aim of this research is to increase interest and learning outcomes in the history of Islamic culture in the material on the development of science during the Abbasid era for students in class XI_IA MAN 2 Aceh Besar for the 2018/2019 academic year. The model used in this classroom action research is the Student Teams Achievement Division (STAD) model. This classroom action research was carried out over a period of 3 months, namely from March 2019 to May 2019 in the Even semester. Classroom action research consists of two cycles and each cycle consists of three meetings, simulations in planning, implementation, observation and reflection activities. The data collection technique is collecting test scores which are carried out at the end of each lesson in each cycle using a question instrument (written test). Observations are carried out by paying attention to students' interests and learning outcomes. Data were analyzed using percentage statistics. The research results showed that there was an increase in student interest and learning outcomes from 42.9% in pre-research, increasing to 71.4% in cycle I and increasing to 90.5% in cycle II. Students' interest in learning increased from the fair to good category and the good category and increased to very good after implementing the student teams achievement division (STAD) model in learning the History of Islamic Culture on material on the development of science during the Abbasid era for students in class XI-IA MAN 2 Montasik Aceh Besar for the 2018/2019 academic year.